Gift or a bribe? : Examining the perception of gift giving - Arntz, Michael (2024)
This thesis firstly sets a theoretical framework, exploring definitions, processes, and perceptions of gifts alongside theories like social exchange, reciprocity, and equity. The study further delves into the evolution of gift giving practices, the cultural influences, distinctions between gifts and bribes, and economic and psychological theories relevant to bribery. In the practical part the thesis empirically examines the factors influencing the ethical perception of gift-giving in professional settings. Utilizing a quantitative approach, the thesis analyzes survey data collected from participants exposed to eight hypothetical scenarios designed to reflect different situational contexts. Each scenario varied key elements such as the value of the gift, the relationship between the giver and the recipient, and the context in which the gift was given to determine how these factors affect perceptions of whether an item is considered a gift or a bribe. The analysis was conducted using a linear mixed model to assess the impact of these variables on perception outcomes. The result showed that the context under which a gift is given heavily influences the perception. Higher value compared to lower, monetary form of the gift compared to a gift in-kind and a distant relationship compared to a friendly one all raised the likelihood of a gift being perceived as a bribe. The findings provide valuable insights for developing clearer guidelines and policies that help professionals navigate the ethical challenges of gift-giving and bribery.